Las Claustrillas de Las Huelgas, San Andrés de Arroyo y Aguilar de Campo: los repertorios ornamentales y su eclecticismo en la escultura del tardorrománico castellano - Hernando Garrido, José Luis (Anuario del Departamento de Historia y Teoría del Arte, 1992)
In spite of the grand volume of work dedicated to the famous Cistercian abbey of Las Huelgas, located in the province of Burgos, its oldest dependence, Las Claustrillas, has hardly been studied in a global analysis. In this section is condensed a grand variety of ornamental motives, all of them from late Romanesque. Although its sculptors assume the inheritance from the great experts in the last third of XIIth century, we are not partisans to attribute to Master Ricardo -who appears between the documents in the monastery in 1203- the particular sculptoric development in Aguilar de Campoo, S. Andrés de Arroyo and other groups from Palencia. These pages will be too about placing some characteristic elements of Castilian late Romanesque with regard to the European contemporaries.